Співвідношення понять "правовий захист" та "охорона права" у науковому дискурсі - Бабич, Я. С. (Київський національний університет імені Тараса Шевченка, 2021)
Розглянуто й досліджено юридичні категорії "правовий захист" та "охорона права". Проаналізовано правову природу і зміст цих визначень. Особливу увагу приділено характеристикам цих дефініцій у науковій міжнародній і вітчизняній доктринах. Розглянуто позиції п'яти різних наукових шкіл щодо розуміння означених понять. Перша когорта науковців дотримується поглядів, за якими такі дефініції аналізуються як взаємодія частини та цілого. Друга група вчених ототожнює поняття "правовий захист" та "охорона права". Третій погляд на означену теоретичну проблематику полягає у розмежуванні окреслених визначень. Четверта плеяда науковців розкриває аналізовані категорії крізь призму окремих галузей права, зважаючи на предмет і метод правового регулювання кожної окремої сфери. Універсальний підхід розмежовує поняття "правовий захист" і "охорона права" й розглядає їх як різні та водночас абсолютно повноцінні юридичні категорії. Обґрунтовано, що останній має нормативно-прикладне значення й результативно використовується міжнародним співтовариством як на доктринальному, так і на законодавчому рівні. На підставі проведеного теоретичного дослідження запропоновано самостійні наукові висновки та судження з аналізованої тематики, зокрема надано авторське визначення дефініції "правовий захист". Крім того, виокремлено основні ознаки, притаманні вищезгаданим категоріям. Особливу увагу наголошено на необхідності виділення превентивної складової поняття "правовий захист", яка має особливо важливий характер у межах означеної категорії.

The article addresses the understanding of the legal categories "legal protection" and "protection of rights". The legal nature and content of these definitions are analyzed. Particular attention is paid to the characteristics of these definitions in scientific international and domestic doctrines. The positions of five different scientific schools on the understanding of these concepts are considered. The first cohort of scientists adheres to the views according to which such definitions are analyzed as interaction of whole and part. The second group of scholars identifies the concepts of "legal protection" and "protection of rights". The third point of view on the specified theoretical problems, consists of the delimitation of the outlined definitions. The fourth constellation of scholars reveals the analyzed categories through the prism of individual branches of law, taking into account the subject and method of legal regulation of each area. The universal approach distinguishes between the concepts of "legal protection" and "protection of rights" and considers them as different, but at the same time absolutely full-fledged legal categories. It is substantiated that the latter has normative and applied significance and is effectively used by the international community both at the doctrinal and legislative levels. On the basis of the conducted theoretical research the independent scientific conclusions and judgments on the analyzed subjects are offered, in particular the author's definition of definition "legal protection" is given. In addition, the main features inherent in the above categories are highlighted. Particular attention is paid to the need of highlighting the preventive component of the concept of "legal protection", which is particularly important within this category.
Relationship of Concepts "Legal Protection" and "Protection of Rights" in Scientific Discourse
Keywords: правовий захист; охорона права; права людини; відновлення порушених прав; недопущення правопорушення; превентивний характер; legal protection; human rights; restoration of violated rights; prevention of offenses